2023
DOI: 10.3390/membranes13020252
|View full text |Cite
|
Sign up to set email alerts
|

Research on Membranes and Their Associated Processes at the Université Paris-Est Créteil: Progress Report, Perspectives, and National and International Collaborations

Abstract: Research on membranes and their associated processes was initiated in 1970 at the University of Paris XII/IUT de Créteil, which became in 2010 the University Paris-Est Créteil (UPEC). This research initially focused on the development and applications of pervaporation membranes, then concerned the metrology of ion-exchange membranes, then expanded to dialysis processes using these membranes, and recently opened to composite membranes and their applications in production or purification processes. Both experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 177 publications
0
1
0
Order By: Relevance
“…It should be observed that, electrochemical potentials are recognized through membranes due to uneven charge allocations (Kisnieriene et al, 2019). Discrepancies between membrane potentials and actual potentials formed by non-equilibrium allocations is a degree of quality of energy needed (Fageria et al, 2006;Baklouti et al, 2023). Electrical charge , therefore could be computed by means of a revised Nernst equation explained by Ting (1982), as stated below: Ψ = (-RT/ZF/In (ai/a0) Where Ψ = electrochemical potential between root cells and external solutions in mullivolts (MV); R = gas constant (8.3J/mol K); T = absolute temperature (K); Z = net charge on ion (dimension less); F = Faraday constant (96, 400 J/mol); ai = activity of ion inside a tissue, and a0 = activity of ion outside a tissue.…”
Section: Active and Passive Ion Transportsmentioning
confidence: 99%
“…It should be observed that, electrochemical potentials are recognized through membranes due to uneven charge allocations (Kisnieriene et al, 2019). Discrepancies between membrane potentials and actual potentials formed by non-equilibrium allocations is a degree of quality of energy needed (Fageria et al, 2006;Baklouti et al, 2023). Electrical charge , therefore could be computed by means of a revised Nernst equation explained by Ting (1982), as stated below: Ψ = (-RT/ZF/In (ai/a0) Where Ψ = electrochemical potential between root cells and external solutions in mullivolts (MV); R = gas constant (8.3J/mol K); T = absolute temperature (K); Z = net charge on ion (dimension less); F = Faraday constant (96, 400 J/mol); ai = activity of ion inside a tissue, and a0 = activity of ion outside a tissue.…”
Section: Active and Passive Ion Transportsmentioning
confidence: 99%